The Impact of Social Environment on the Sexual Self-Regulation of University Students in Uganda - Musa Muwaga; Fuad Nashori; Achmad Sholeh (International Journal of Islamic Educational Psychology, 2020)
Most societies consider sexual self-regulation to represent a general temptation control mechanism, postponing gratification. This study aims to determine the social environment's impact on university students' sexual self-regulation in Uganda. The data were obtained using convenience technique sampling of undergraduate students at university "X" in Uganda. Students voluntarily completed the questionnaire in a regular classroom setting. The questionnaire elicited information regarding sexual regulative capacities like seeking accurate information from social environments like family, peer, and university environments. The data were analyzed using both univariate analyses (chi-square and analysis of variance and logistic regression. The results indicated that the social environment had a positive and significant relationship with sexual self-regulation and university students with a value of 1t1 ≥1.96, and factor loading≥0.50 was significant. These results should be considered by those working with university students in human sexuality and human development